A estética da pulsão de morte na conscientização ambiental: paradoxos e sintomas do imaginário ecológico - Corbucci, Fabiola (2011)
The relative (in)efficiency of environmental awareness programs carried out by various communication media is considered here as a social symptom in which great success and failure paradoxically coexist. This research investigates one type of image related to this thematic communication with the purpose of discussing the imaginary on which it draws. We note that there is a type of image that fits into the aesthetics of the death drive: at the indexical level it portrays degraded environments and apocalyptic phenomena; at the iconic level it recurs to a plasticity that mimics the qualities of death. Why is this type of image presented even when the subject it addresses intends to promote the continuity of life? This question led us to analyze of the iconicity (Peircean semiotics) of the catastrophic images transmitted by the media as revealing a thanatophilic imaginary and promoting an interpretant that invites the observer to contemplation, inertia, and the Nirvana. With this purpose, the relative inoperativeness of populations concerning environmental movements emphatic demand for a radical transformation in their ways of life is questioned. This relative inoperativeness, announced not only in environmental reports, but also in the media, is surprising in view of the widespread dissemination of the ecological issue in urban societies at least since the 1960s. We interpret this paradoxical gap in the environmental movement as a social symptom and relate it to the thanatophilic imaginary manifested in the images of the environmental campaign and generalized through the media. We draw on the social, political, and cultural context of modern capitalism with the purpose of better understanding how the representation of nature is implicated in the daily practices of urban societies. We reflect on the vicissitudes of a glocalizing process of civilization for the effectiveness of the human relation to nature. With this in mind, we carry out a theoretical and interpretive discussion of the visual communication accomplished by the environmental campaign, especially in its psychic and imaginary dimensions. We investigated the discourse of this widespread environmental campaign based on an analysis of its images in order to make evident latent points or aspects and, thus, interpret inoperativeness concerning the environmental threat. The theories of Peirce and Freud have been fundamental for our analysis, as well as reflections by other authors, such as Keith Thomas, José Augusto Pádua, Eugênio Trivinho, Vladimir Safatle, and Slavoj i ek. Concepts such as sign (especially icon and index, but also symbol), imaginary, fetishism, the unconscious, and death drive are also central to our analysis